PERSEPSI TENAGA PENDIDIK TERHADAP PEMBELAJARAN DARING SELAMA MASA PANDEMI: SEBUAH STUDI DI INSTITUSI NEGERI - Azhar Aziz Lubis; Fitra Youpika (Wacana: Jurnal Penelitian Bahasa, Sastra dan Pengajaran, 2022)
This descriptive qualitative research investigated lecturers’ perception on online learning during the COVID-19 pandemic era. This turned out that most of the lecturers are keen on running the teaching and learning activities online despite some problems which might repeatedly occurred during the class. However, most of the participants think that the online learning is difficult to do albeit they like it. Then, discussion is the most favorable method to do in the online learning activities. Some possible suggestions for future actions is needed.